A meta‐analysis of the effect of chromium supplementation on anthropometric indices of subjects with overweight or obesity. Issue 4 (21st May 2019) - Tsang, Catherine; Taghizadeh, Mohsen; Aghabagheri, Elahe; Asemi, Zatollah; Jafarnejad, Sadegh
Summary: The role of chromium as a weight loss agent remains questionable, and although previous meta‐analyses findings have reported small reductions in body weight in individuals with overweight/obesity following chromium supplementation, there have been significant limitations with these findings. The objective of this meta‐analysis was to evaluate the current evidence for the efficacy of oral chromium supplementation in individuals with overweight/obesity from randomized controlled trials. Studies were identified by a search of electronic databases from inception to November 2018 and combined and stratified analyses were used. Twenty‐one trials from 19 studies were identified which met all inclusion criteria which were suitable for statistical pooling, and data from 1316 participants were included. Pooled analysis showed significant reductions in anthropometric indices associated with body composition; for weight loss (weighted mean difference [WMD]: −0.75 kg, 95% confidence interval [CI], −1.04, −0.45, P  < 0.001), body mass index (WMD: −0.40, 95% CI, −0.66, −0.13, P  = 0.003 and body fat percentage (WMD: −0.68%, 95% CI, −1.32, −0.03, P  = 0.04) in individuals with overweight/obesity. No changes were detected in controls. Subgroup analysis showed significant improvements in weight loss and body fat percentage, particularly for study durations ≤12 weeks and doses ≤400 μg/d. Chromium supplementation was associated with some improvements in body composition in subjects with obesity/overweight. The effect size was medium and the clinical relevance of chromium as a weight loss aid remains uncertain. Further investigation from larger and well‐designed randomized controlled studies, especially in patients with diabetes, is warranted.